Sustainable Urban Farming Rack Design Using Eco Friendly Materials with Variety Load - Rahmat; Ade Hermawan; Dean Anggara Putra (Jurnal Keteknikan Pertanian, 2025)
Vertical farming requires a structurally sound and environmentally sustainable racking system; however, existing research largely neglects the evaluation of the structural safety of eco-friendly racking materials under various operational loads. This gap necessitates further rigorous mechanical performance assessments to ensure the long-term reliability of the system. This study aims to develop a vertical farming racking design with an adequate safety factor by examining its structural response to various load scenarios. A design-construction methodology supported by SolidWorks simulations was used to evaluate stress distribution, strain behavior, and deformation patterns. Simulation results using SolidWorks software indicate that the maximum compressive stress at the loaded joint surface is 13.734 MPa, while the minimum stress is 1.149 MPa. The highest load occurs at the fourth (bottom) joint level due to pump-induced water pressure. The maximum strain recorded is 0.00491, with a minimum of 0.00041. The top shelf level exhibits a maximum displacement of 48.165 mm, while the minimum displacement is 0 mm. This shows that the material and shape of the frame that has been made are in the safe category with a safety factor (sf) of 2.4. These findings indicate that the proposed rack design maintains structural integrity within safe limits and is suitable for application in vertical farming systems.